Implementasi Steganografi Menggunakan Metode Least Significant Bit dan Kriptografi Advanced Encryption Standard - Shinta Puspita Sari; P.M. Winarno; Dodick Z. Sudirman (Ultimatics : Jurnal Teknik Informatika, 2012)
Nowadays, the development of celluler device especially mobile phone is very rapid. The security of information in mobile phone becoming such an important thing, because users do not want other people can access their essential information. It means in the security in mobile phone. One way to secure the data is steganograpgy technique. This technique hides the data in a digital media. In this research the steganography technique that the is used is the Least Significant Bit (LSB) which implemented to cellular equipment with android as the operating system. The digital image which is used to hide the data is PNG. The test result shows that steganography has been implemented successfully in android phone. In the imprecebility aspect, user cannot different between the picture with message and the original picture bare eyedly. In recovery aspect, the message successfully encrypted and decrypted without changing the original content of the message. The lack occurs in fidelity aspect which the expansion of PNG file happens. Index Terms—LSB, least significant bit, png, android, handphone